Studi Kasus Pemeriksaan MSCT Urografi Multiphase dengan Klinis Tumor Ginjal - Ratna Tri Rahayu; Nanang Sulaksono; Andrey Nino Kurniawan (Poltekkes Kemenkes Semarang, 2023)
Background: The procedure for examining multi-slice computed tomography (MSCT) multiphase urography with clinical kidney tumors in the Radiology Installation of the Banyumas General Hospital differs from the literature in the use of scans in the corticomedullary phase and the post-contrast scanning phase. This study aims to determine the procedure for MSCT Urography Multiphase examination with clinical kidney tumors, to find out the reasons for using a scan of the corticomedullary phase area from the diaphragm to the pubic symphysis and to find out the reasons for using four phases of post-contrast scanning.Methods: This type of research is qualitative research with a case study approach. Data was collected at the radiology installation at the Banyumas Hospital from January to May 2023, the study respondents consisted of three radiographers, one radiologist, one sending doctor and one radiology nurse. Methods of data collection by observation, in-depth interviews, documentation. Data analysis was carried out through the stages of data collection, data reduction, data presentation and drawing conclusions.Results: MSCT Urography Multiphase examination procedure with clinical kidney tumors in the radiology installation of Banyumas Hospital includes, the patient's supine feet first position, scanning area from the diaphragm to the symphysis pubis, using 50 ml of contrast media with 40 ml of saline flush. Scanning technique by taking the pre-contrast phase, corticomedullary phase, nephrography phase, equilibrium phase and delay phase. Scan the area of the corticomedullary phase from the diaphragm to the symphysis pubis to to simplify the scanning process because the tool protocol has already made full abdominal scan area settings and to evaluate the pattern of abdominal organ enhancement if there is a metastatic urothelial lesion other than the kidney. The use of four phases of post-contrast scanning is because the goals and functions of each scanning phase are different so that the maximum diagnostic information is obtained.Conclusions: The MSCT Urography Multiphase examination procedure with clinical kidney tumors in the radiology installation of Banyumas can provide optimal diagnostic information.